SOLUSI TEKNOLOGI INFORMASI SEBAGAI PEMBANGUN SISTEM INFORMASI - Yulianto, Yulianto (Jurnal Ilmiah Infokam, 2005)
Autoimmunization, speed, and the good accuracy in conducting process of calculation and also distribution of information have come to determinant for breathing live, grab market and win competition. Information will have come to blood in company life. Without information, head cannot know objective condition its company, so that cannot compile strategy which the exact to increase ability of company in yielding profit. Develop; Building an information system have come to requirement insisting on, because that system determining where from data in obtaining, processed, and yield information. Groove effective system of will determine information quality.   Keyword: Technology Information and System Information.